Another one breathes the dust. The relation between severe air pollution episodes and school attendance in southern Chile. Issue 2 (1st February 2021) - Hofflinger, Álvaro; Boso, Àlex
ABSTRACT: The intermediate-sized cities of southern Chile experience days of high pollution levels every winter due to the use of wood-burning stoves. Several studies have analysed the factors that hinder energy transition and the social acceptance of measures to improve air quality, the consequences of which are disturbing. However, they have mainly focused on health issues without considering the social impacts of air pollution. This study aims to assess whether exposure to outdoor air pollution is associated with school absenteeism. We analysed the records of approx. 5, 000 students in the fourth grade from 25 schools in five cities in southern Chile (2010–2017). Using a fixed-effects model and applying it to the school level, we were able to estimate the effect of air pollution on absenteeism from school after controlling for the effects of individual characteristics. Previous studies have found that independent of air pollution, students from low-income families have a higher absenteeism rate. Our findings suggest that as air pollution worsens, pupils from middle and high-income households are also more likely to miss school days. We argue that this is, presumably, because high-income families are able to develop protective behaviour such as bringing their children to the doctor or keeping them at home on highly polluted days.